On the Lystrosaurus zone and its fauna with special reference to some immature Lystrosauridae - Kitching, J. W. (Bernard Price Institute for Palaeontological Research, 1968)
In the past, collecting from the middle Beaufort Beds or Lystrosaurus zone has been badly neglected by field workers mainly due to the monotonous occurrence of the genus Lystrosaurus. Collecting has mostly been undertaken in such areas as the Harrismith Commonage, Oliviershoek Pass, Bergville or where there was a good possibility of finding either Thrinaxodon, Glochinodontoides or other faunal remains more exciting than Lystrosaurus.
Main article
Keywords: Lystrosaurus zone; Lystrosauridae